Community Archives Digitization, Access, and Preservation Partnership: Catalyst Fund Final Report - Carlson, Doug; Davis, Deborah; Suttles, Dallas (Valdosta State University Archives and Special Collections, 2024)
Carlson, Douglas and Deborah Davis. “Community Archives Digitization, Access, and Preservation Partnership: Catalyst Fund Final Report.” August 2024. Valdosta State University Archives and Special Collections.
Lyrasis Grant White Paper
Keywords: Corporation reports